TI_GERICHTE 52.2005.246 vom 26. September 2005 , procedura ad invito: concorso per l'assegnazione del mandato di elaborazione di un PR - TI Tribunale d'appello (2005)
procedura ad invito: concorso per l'assegnazione del mandato di elaborazione di un PR